10.1016/s0967-0653(98)80138-5 (CrossRef Listing of Deleted DOIs, 2000)
Background Cardiorespiratory fitness (CRF) is reduced in patients with psoriatic arthritis (PsA), highlighting the need for a consistent assessment of CRF in clinical practice. This study aimed to examine the associations between outcomes of clinical field tests, namely six-minute walk test (6MWT) and handgrip strength (HGS), and CRF, as well as to evaluate the accuracy of these clinical field tests in detecting impaired CRF in patients with PsA. Methods Distance walked during 6WMT (6MWD), HGS by hand dynamometry, and maximal CRF as peak oxygen uptake (VO 2 peak, ml/min/kg) by cardiopulmonary exercise testing were assessed. 6MWD and HGS were compared to reference charts of the general population using one-sided t-tests. Spearman's rank correlation coefficients (r s ), multivariable linear regression models and receiver operating curves were analysed to study associations. Results In 80 PsA patients, 6MWD was strongly associated with VO 2 peak (r S =0.65, p<0.001), with the multivariable linear regression model, consisting of 6MWD and 6MWT heart rate response and adjusted for relevant covariates, explaining 70% of variance in VO 2 peak. The threshold of 108%predicted 6MWD had sensitivity of 75% and specificity of 64% to identify patients with impaired CRF. 6MWD and HGS were not significantly decreased compared to the general population (p>0.05). A higher 6MWD was moderately to strongly correlated with more favourable outcomes regarding disease activity, cardiometabolic risk, and patient-reported outcomes. No or only weak associations between HGS and VO 2 peak as well as clinical outcomes were noted. Conclusions 6MWD was strongly associated with VO 2 peak, moderately to strongly correlated with important clinical outcomes and had adequate accuracy to detect patients with impaired CRF.